Environment-friendly rubber asphalt material prepared by synergism of multiple solid wastes and preparation process of environment-friendly rubber asphalt material
Through the multi-solid waste collaborative preparation process, high-strength, water-permeable multi-solid waste ceramics are prepared using solid waste raw materials such as copper tailings, garbage incineration fly ash, Baiyun tailings and wood chips, and mixed them in concert with other materials to form rubber asphalt materials with excellent mechanical properties and environmentally friendly, which solves the problems of poor durability and insufficient rut resistance in the existing permeable asphalt pavement, and achieves efficient resource utilization and environmental protection.
Patent Information
- Application Number
- CN202411755654.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing permeable asphalt pavement is prone to loose and pits and other structural diseases under load, and has poor durability. It lacks a rubber asphalt material that uses a variety of solid waste raw materials to maintain high water permeability on the road and has high resistance to ruts and deformation resistance.
Environmentally friendly rubber asphalt materials prepared in a coordinated manner by using copper tailings, garbage incineration fly ash, Baiyun tailings and wood chips are prepared through granulation, preheating and sintering processes such as granulemaking, preheating and sintering, and are mixed with elastomeric modified asphalt, waste rubber powder, stabilizers, anti-flaking agents and tackifiers to form rubber asphalt materials with excellent mechanical properties and environmentally friendly.
The high water permeability and mechanical strength of rubber asphalt materials have been achieved, the resistance to rut and deformation resistance is enhanced, and the pollution of solid waste raw materials to the environment is reduced, and there are significant economic and environmental benefits.
Smart Images

Figure BDA0005166206910000111 
Figure BDA0005166206910000112 
Figure BDA0005166206910000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of road engineering materials, and more specifically, to an environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes and a preparation process thereof. Background Art
[0002] Rubber asphalt is an asphalt binder material processed from waste tires. It has the advantages of high temperature stability, low temperature flexibility, anti-aging, fatigue resistance, and water damage resistance. It is an ideal environmentally friendly pavement material. It is mainly used in the prestressed absorption layer and surface layer in the road structure. It can effectively improve the service life of the road surface, reduce noise, reduce vibration, and resist thermal cracking and low temperature cracking. Rubber asphalt can not only provide high-quality construction materials for road engineering construction and save petroleum asphalt resources, but also solve the solid waste digestion channel of waste rubber tires "turning waste into treasure". Therefore, the production of rubber asphalt with tire rubber powder has good economic and social benefits.
[0003] At present, permeable asphalt pavement is an important pavement form in the construction of sponge city roads, which can significantly reduce rainwater runoff, enhance the pavement anti-skid coefficient, and improve road traffic safety. Traditional permeable asphalt pavement often has structural defects such as looseness and potholes under load due to the low mechanical strength of aggregates; at urban intersections or heavy traffic sections, it is more likely to have deformation and damage such as rutting, congestion, and cracks. Therefore, conventional permeable asphalt pavement has the defect of poor durability as a whole.
[0004] At present, there are many types of solid waste produced in industrial production with complex components, such as blast furnace slag, steel slag, metal slag, slag, coal gangue, etc. In order to achieve the rational utilization of resources and sustainable development of the environment, the application of solid waste to road construction is a common method. However, solid waste is mostly used alone. For example, CN2019109400971 discloses a high-strength and durable steel slag permeable asphalt pavement structure, and CN2020111469403 discloses a coal gangue asphalt mixture. Therefore, there is currently a lack of a rubber asphalt that utilizes multiple solid waste raw materials to keep the road highly permeable while still having high resistance to rutting and deformation. Summary of the invention
[0005] In order to make the rubber asphalt material have higher water permeability and mechanical strength and recycle a variety of solid wastes at the same time, the present application provides an environmentally friendly rubber asphalt prepared by synergistic use of multiple solid wastes and a preparation process thereof.
[0006] In the first aspect, the present application provides an environmentally friendly rubber asphalt material prepared by synergistically preparing multiple solid wastes, using the following technical solution:
[0007] An environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes, comprising the following raw materials in parts by weight: 100-140 parts of elastomer-modified asphalt, 15-25 parts of waste rubber powder, 0.5-1 part of SBR, 1-3 parts of stabilizer, 1.5-3 parts of anti-stripping agent, 30-50 parts of multiple solid waste ceramsite, 10-14 parts of aromatic oil, and 5-15 parts of tackifier;
[0008] The waste rubber powder is made by mixing and crushing waste tires and EPDM rubber in a mass ratio of 1:0.3-0.5;
[0009] The multi-solid waste expanded clay is prepared by adding water to solid waste raw materials to form wet materials, followed by granulation, drying, preheating at 340-350° C. for 20-30 minutes, and sintering at 1050-1100° C. for 20-30 minutes. The solid waste raw materials include copper tailings, domestic waste incineration fly ash, white cloud tailings and wood chips in a mass ratio of 9:1:0.25-0.5:0.6-1.
[0010] By adopting the above technical scheme, rubber powder is added to the elastomer modified asphalt. The rubber powder is a powder material with a cross-linked structure. The rubber powder contains carbon black. The carbon black is uneven. The carbon black molecules have very active activation points and unpaired electrons, which can react chemically with the asphalt. The asphalt is adsorbed on the surface of the carbon black and chemically combined, so that the asphalt is adsorbed on the surface of the carbon black and moves with the carbon black, forming a strong bond that can slide between the carbon black and the asphalt, thereby realizing the reinforcement of the elastomer modified asphalt by the carbon black.
[0011] The main components of copper tailings are silicon dioxide, calcium oxide, iron oxide and magnesium oxide, while the content of silicon dioxide and aluminum oxide in copper tailings is relatively small, so it is necessary to add waste incineration fly ash to adjust the silicon dioxide and aluminum oxide in the tailings. Domestic waste contains a large amount of chlorine, and the incineration process will cause the redistribution of heavy metals and chlorine in the waste, resulting in a higher pollutant concentration in the fly ash than incineration bottom ash. The fly ash has a small particle size, a large specific surface area, and is hygroscopic and fluttering. The main component is calcium oxide, followed by silicon dioxide, aluminum oxide and iron oxide. Dolomite tailings contain calcium fluoride, silicon dioxide, ferric oxide, dolomite, barium sulfate and sodium pyroxene. The fluoride and alkali metal compounds therein are conducive to the formation of liquid phase at low temperature during the sintering process, reducing the sintering temperature and improving the strength of multi-solid waste ceramsite. The decomposition of carbonate during the sintering process is conducive to increasing the porosity of multi-solid waste ceramsite and improving water permeability. The three are used in combination to adjust the silicon dioxide and aluminum oxide components in the ceramsite, and exist in the ceramsite in the form of crystal structure and glass phase. , after a series of complex chemical and physical reactions, mullite crystals are formed, which are the main component of ceramsite with mechanical strength. However, the content of silicon dioxide and aluminum oxide should not be too high. Too high will cause the sintering temperature of ceramsite to be high, or even explode. Therefore, the amount of copper tailings, waste incineration fly ash and white cloud tailings is adjusted to make the product quality of ceramsite stable. Moreover, if the content of alkali metal oxides such as calcium oxide and magnesium oxide in fluxing components is too high, more liquid phase substances will be produced during sintering of ceramsite, which will fill the internal pores, so that the porosity of ceramsite will be reduced and the particle density will be increased. Sawdust is used as the gas-producing component, which contains a certain amount of organic matter or carbonate, which will be decomposed by heat at high temperature to produce carbon dioxide. At the same time, the viscous liquid phase substance produced by the fluxing component, as the amount of carbon dioxide and liquid phase increases, the carbon dioxide will be wrapped by the liquid phase substance, causing the ceramsite to expand, and a hollow structure will be formed in the internal space of the ceramsite. However, if there is too much gas-producing component, the interior of the ceramsite will be broken due to excessive expansion and too many holes. If there is insufficient gas-producing component, the ceramsite will not expand during sintering.
[0012] After granulation and drying, the solid waste raw materials are preheated, which can gradually heat the expanded clay. When entering the sintering stage, it will not explode due to sudden high temperature. When the preheating time is extended, it will decompose or produce organic matter and carbonates, etc., so that the expanded clay has a certain viscosity after entering the sintering stage, the gas generated is reduced, the expansion is reduced, and the density is increased, which is beneficial to improve the strength of the expanded clay. After sufficient preheating, it enters the sintering stage. A large amount of gas is generated inside the expanded clay, and a large amount of liquid phase appears on the surface. The gas generated inside is wrapped by the surface liquid phase to form a porous structure. The excess liquid phase is bonded and filled in the pores of the expanded clay raw material particles, which increases the strength of the expanded clay, thereby obtaining a large specific surface area, high water absorption rate, high cylinder pressure strength, light weight, frost resistance, corrosion resistance, sound absorption and noise reduction, thermal insulation and other advantages, thereby improving the permeability of rubber asphalt while enhancing its compressive strength, improving rutting resistance and deformation resistance.
[0013] Optionally, the method for preparing the multi-solid waste ceramsite is as follows:
[0014] The copper tailings are mixed evenly with waste incineration fly ash, Baiyun tailings and wood chips to obtain solid waste raw materials;
[0015] Adding 20-30 wt% of water to the solid waste raw material and mixing them evenly to form a wet material;
[0016] Granulating the wet material to obtain raw material balls with a particle size of 5-9 mm;
[0017] The raw material balls are dried at 100-110° C. for 4-5 hours, then preheated at 340-350° C. for 20-30 minutes, and sintered at 1050-1100° C. for 20-30 minutes to prepare multi-solid waste ceramsite.
[0018] By adopting the above-mentioned technical scheme and utilizing copper tailings, waste incineration fly ash, Baiyun tailings and sawdust as raw materials to calcine expanded clay, expanded clay with pore structures of different sizes and shapes can be produced, which can greatly reduce the pollution to the land, water bodies and the environment, solve the problem of occupying land resources due to landfill accumulation, promote the treatment of solid waste and the realization of my country's dual carbon goals, and have obvious economic and environmental benefits.
[0019] Optionally, the multi-solid waste ceramsite is pretreated as follows:
[0020] Dissolve sodium chloride to prepare a sodium chloride solution with a concentration of 15-20wt%, add sodium dodecyl sulfate, mix evenly, and obtain a soaking solution, wherein the mass ratio of sodium dodecyl sulfate to sodium chloride is 0.015-0.025:1;
[0021] Adding the solid waste ceramsite into the soaking solution, soaking for 5-7 hours at 35-45°C, filtering and drying to obtain the salt-loaded ceramsite;
[0022] Mix anhydrous ethanol and distilled water in a mass ratio of 55-60:1, adjust the pH to 2-3, add 6.5-6.7% of hexadecyltrimethoxysilane by mass, stir at room temperature to obtain a spray liquid, spray the spray liquid evenly on the salt-loaded ceramsite, and let it stand at room temperature for 20-24 hours. The mass ratio of the spray liquid to the salt-loaded ceramsite is 0.1-0.2:1.
[0023] By adopting the above technical scheme, the porous foaming structure inside the multi-solid waste ceramsite is dense and uniform, has good adsorption performance, and has rich macroscopic structure on the surface, which is rough and irregular. It is soaked in a sodium chloride solution with a concentration of 15-20wt% at 35-45°C. At this concentration and temperature, the molecular movement rate in the solution is accelerated, and the adsorbed sodium chloride can overcome the liquid film resistance on the surface of the multi-solid waste ceramsite, which is conducive to the migration of sodium chloride along the micropores of the multi-solid waste ceramsite to the inside. Moreover, under the action of sodium dodecyl sulfate, the solid-liquid-gas interface state is improved, and the contact angle is reduced, so that it can better infiltrate and spread in the internal voids of the multi-solid waste ceramsite. After the soaking and adsorption are completed, it is dried to make the sodium chloride continuously crystallize in the multi-solid waste ceramsite, and the condensed and solidified sodium chloride is interlocked with the multi-solid waste ceramsite, which strengthens the ceramsite to sodium chloride. Adsorption makes the expanded clay and sodium chloride adhere tightly to ensure the stability of sodium chloride. Sodium chloride is continuously released in the asphalt material, inhibiting freezing and reducing freeze-thaw quality and strength loss. Hexadecyltrimethoxysilane is hydrolyzed to form hexadecylsilanol, which has three terminal hydroxyl groups. The three terminal hydroxyl groups can undergo intermolecular condensation reaction with the hydroxyl groups on the salt-loaded expanded clay to form silicon-oxygen chemical bonds, forming a hydrophobic film on the surface of the salt-loaded expanded clay, reducing the absorption of water by the expanded clay, reducing the retention in rubber asphalt, and reducing cracking caused by low-temperature ice crystal expansion. Moreover, hexadecyltrimethoxysilane is easily hydrolyzed and condensed to form polysiloxane, which has a strong tolerance to chemical substances such as acids, alkalis and salts, so that it has a better protective effect in a saline environment, and can reduce the corrosion of salts such as sodium chloride to multi-solid waste expanded clay and rubber asphalt materials.
[0024] Optionally, the anti-stripping agent is hydrophobically modified polyester fiber.
[0025] In winter, when moisture penetrates into the road surface, the physical frost heave effect of water causes the road surface to be subjected to expansion pressure generated by water crystallization. After repeated freezing and thawing, the overall stability of the internal structure is damaged to a certain extent. In addition, in winter, the road surface is frozen. When salt-based de-icing agents are used, the salt expands on the road surface due to freezing, which will further increase the damage to the road surface. By adopting the above technical scheme, the hydrophobic modified polyester fiber can be evenly distributed in the rubber asphalt and form a fiber mesh structure, which increases the viscosity of the rubber asphalt, enhances the cohesion of the asphalt material, and increases the grip of the asphalt on the multi-solid waste ceramsite, so that the voids of the mixed material are well filled. If the asphalt needs to be stripped, a larger interfacial energy is required, so it can effectively alleviate the erosion of the salt solution and the stripping effect of the crystal expansion on the interface bonding between the asphalt and the aggregate. The polyester fiber has load transfer capacity and balancing effect in the asphalt mixture, and can disperse the external load in the multi-solid waste ceramsite and rubber asphalt, thereby improving the toughness of the rubber asphalt. The three-dimensional multi-directionally distributed polyester fibers overlap each other, showing a good bridging and reinforcement effect. When the rubber asphalt is anti-icing at low temperatures using snow-melting salt, It can prevent the formation and expansion of cracks and damage when expansion cracks and damage are generated by the freeze-thaw cycle of salt solution, and can also fill gaps, increase density, and reduce freeze-thaw corrosion resistance; the fiber ends are connected to the asphalt to form tentacles, which have the effect of anchoring and interlocking the internal structure of the asphalt material. The fiber surface and the fiber root are firmly bonded to the asphalt material, thereby strengthening the asphalt structure and obtaining a high-strength interface layer. On the whole, the polyester fibers overlap each other in the asphalt material to form a dense, high-tensile strength spatial network structure, which fully plays the role of reinforcement, toughening and crack resistance, and can also limit the mutual slippage of the interface of multiple solid waste expanded pellets. In addition, the hydrophobically modified polyester fiber absorbs less water, which is convenient for water penetration and is not retained in the rubber asphalt pavement, reducing the impact of water expansion on the pavement.
[0026] Optionally, the preparation method of the hydrophobically modified polyester fiber is:
[0027] The silane-modified silica particles are mixed with butyl acetate, and ultrasonically dispersed for 20-30 minutes, and polyurea resin and curing agent are added, and stirred evenly to obtain a treatment liquid;
[0028] The treatment liquid is sprayed on the polyester fiber, and dried at 80-85° C. for 8-10 hours to obtain the modified polyester fiber.
[0029] By adopting the above technical scheme, the urea groups in the polyurea molecule are densely present, and the urea groups are centered on the C=0 group, have extremely strong hydrogen bonding, strong intermolecular force, and have the advantages of corrosion resistance, high wear resistance, scratch resistance, high ductility, etc. After spraying, a super hydrophobic coating is formed on the surface of the polyester fiber, and the silane-modified silica particles are evenly covered on the surface of the polyurea resin, and form a rich micro-nano composite rough structure with the micron-scale skeleton and nano-scale micropores of the polyurea resin, thereby increasing the contact angle of the polyurea hydrophobic coating, making it have better hydrophobic properties, thereby enhancing the antifreeze and stickiness of the coating, and the silica particles are treated with silane hydrophobic modification, which not only increases the particle size and reduces the surface energy, but also improves the formation of The micron-scale wrinkles and the nano-scale roughness of its surface form a secondary composite structure. By capturing air, water droplets are kept in a non-wetted state. The trapped air reduces the interaction between water droplets and the surface of polyester fibers, making it difficult for water droplets to remain on the surface of polyester fibers and can easily slide off its surface, thereby causing water droplets to fall due to gravity and preventing them from freezing on the surface of polyester fibers. In addition, the gas-liquid-solid three-phase contact state on the surface of polyester fibers effectively reduces the heat transfer efficiency, forms a heat-insulating layer, avoids the freezing of water droplets, and prolongs the duration of freezing. In addition, the nanostructured pores formed by silane-modified silica particles reduce the possibility of uneven nucleation of ice crystals, thereby reducing the adhesion of the ice layer and improving the ability to resist freezing and cracking at low temperatures.
[0030] Optionally, the mass ratio of the silane-modified silica particles, butyl acetate, polyurea resin and curing agent is 3-4:8-9:2-3:1-1.5; the mass ratio of the treatment liquid to the polyester fiber is 0.1-0.3:1.
[0031] By adopting the above technical scheme, the dosage of the above raw materials can make the treatment liquid evenly adhere to the surface of the polyester fiber, and the silane-modified silica particles can be firmly and evenly distributed on the polyester fiber, thereby improving the interfacial force between the polyester fiber and the raw materials and enhancing the anti-cracking effect.
[0032] Optionally, the preparation method of the silane-modified silica particles is:
[0033] Anhydrous ethanol and deionized water are mixed, and glacial acetic acid is added to prepare a mixed solution A; anhydrous ethanol, silicon dioxide phase change capsules and tetrabutyl titanate are mixed to prepare a solution B;
[0034] Add solution B to solution A, react at 200-220°C for 20-24h, centrifuge, wash, dry, and calcine at 450-500°C for 2-3h to obtain modified silica phase change capsules;
[0035] Anhydrous ethanol, toluene and perfluorooctyltriethoxysilane are mixed, the pH is adjusted to 9, modified silica phase change capsules are added, ultrasonication is performed for 20-30 minutes, stirring is performed at 60-65° C. for 5-6 hours, centrifugation is performed, washing is performed, and drying is performed to obtain silane-modified silica particles.
[0036] By adopting the above technical scheme, silica phase change capsules are used as carriers, and spherical titanium dioxide materials are loaded on their surface. Moreover, titanium dioxide can be evenly coated on the silica phase change capsules to form a micro-nano structure with a certain roughness, thereby reducing the agglomeration of titanium dioxide and controlling the diameter of titanium dioxide. At the same time, the photocatalytic effect of the silica capsules is improved. When the rubber asphalt material pavement is mechanically damaged or contaminated by organic matter, the super-hydrophobic property can be restored under ultraviolet irradiation. In addition, it has good chemical stability and can reduce salt corrosion.
[0037] The modified silica phase change capsules are hydrophobically modified using fluoroalkyl silanes. Perfluorooctyl triethoxysilane is 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane is an organic silane that can be hydrolyzed and cross-linked in a humid environment to form a solid film with strong hydrophobicity. The three-dimensional waterproof structure of the mesh film effectively prevents the capillary absorption of water by the capillaries, thereby achieving a better waterproof effect. The silicon-oxygen bond has a high bond energy, excellent weather resistance, and a long-lasting waterproof effect. The silane-modified silica particles can have better hydrophobicity and be more evenly dispersed in the polyurea resin, thereby being evenly distributed on the polyester fiber, increasing the roughness of the polyester fiber, improving the interfacial force between the polyester fiber and rubber asphalt, and increasing the crack resistance.
[0038] Optionally, the wall material of the silica phase change capsule is silica, and the core material is tetradecane.
[0039] By adopting the above technical scheme, tetradecane is a solid-liquid phase change material, and silica has good stability. With silica as the shell and tetradecane as the new phase change material, decondensation occurs in an alkaline environment after hydrolysis of ethyl orthosilicate to obtain a highly ordered three-dimensional cross-linked network structure, and the tetradecane is coated. After hydrophobic modification by silane, silica phase change capsules are added to rubber asphalt, so that the rubber asphalt has phase change temperature regulating properties, can achieve anti-icing, reduce the freezing and expansion of water inside the asphalt pavement, reduce the adhesion strength of ice crystals on the asphalt pavement, and easily remove ice after the pavement is frozen.
[0040] Optionally, the tackifier is selected from at least one of petroleum resin, liquid coumarone, terpene resin and rosin resin.
[0041] By adopting the above technical solution, the above tackifying resin can improve the viscosity of rubber asphalt, help to quickly fix and bond during construction, ensure long-term stability and durability, and improve the compatibility of rubber asphalt, avoid stratification and precipitation, and improve heat resistance.
[0042] In the second aspect, the present application provides a preparation process of an environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes, using the following technical solution:
[0043] A preparation process of an environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes, comprising the following steps: mixing elastomer-modified asphalt and aromatic oil, heating to 160-170° C., adding waste rubber, mixing and stirring for 30-40 minutes to obtain a binder;
[0044] The binder temperature is maintained at 160-170°C, and solid waste expanded clay, stabilizer, anti-stripping agent and tackifier are added, mixed and stirred for 40-60 minutes to obtain an environmentally friendly rubber asphalt material.
[0045] In summary, this application has the following beneficial effects:
[0046] 1. Since this application uses solid waste raw materials such as copper tailings, Baiyun tailings and waste incineration fly ash, which are preheated and roasted to produce multi-solid waste expanded clay with high cylinder pressure strength and good water permeability, it can enhance the water permeability of the rubber asphalt material while improving its compressive strength, increase its anti-rutting and anti-cracking capabilities, and reduce the pollution of the solid waste raw materials to the environment.
[0047] 2. In the present application, it is preferred to load sodium chloride in the multi-solid waste expanded clay by solution impregnation, and then use hexadecyltrimethoxysilane for hydrophobic treatment to increase the anti-icing effect of the multi-solid waste expanded clay in winter, reduce the retention of water in the asphalt material, and thus improve the freeze-thaw resistance of the asphalt pavement.
[0048] 3. The present application preferably uses hydrophobically modified polyester fiber as an anti-stripping agent, which can form a fiber network structure, increase the interfacial interaction force between the raw materials, and at the same time delay the erosion of salt de-icing agents, reduce the expansion cracks caused by salt condensation in winter, enhance the toughness and crack resistance of asphalt materials, and improve freeze-thaw resistance. DETAILED DESCRIPTION
[0049] The following examples further illustrate the present application in detail.
[0050] Preparation Examples 1-4 of Multi-Solid Waste Ceramsite
[0051] The fly ash from the incineration of domestic waste in Preparation Example 1-2 is selected from a waste incineration power plant, wherein the dioxin content is ≤10ng-TEQ / kg, there is no risk of dioxin poisoning, the density of sawdust is 530kg / m3, the ignition point is 220°C, the main chemical components of the copper tailings are shown in Table 1, and the main chemical components of the Baiyun tailings are shown in Table 2.
[0052] Preparation Example 1: (1) 900 g of copper tailings, 100 g of fly ash from the incineration of domestic waste, 50 g of Baiyun tailings and 100 g of sawdust were mixed evenly, and dried at 180° C. for 2 h to obtain a solid waste raw material;
[0053] (2) adding 30 wt% of water to the solid waste raw material and mixing them evenly to form a wet material;
[0054] (3) granulating the wet material to obtain raw material balls with a particle size of 9 mm;
[0055] (4) The raw material balls were dried at 110°C for 4 h, then preheated at 350°C for 20 min, and sintered at 1050°C for 30 min to produce more solid waste ceramsite.
[0056] Table 1 Main chemical components of copper tailings
[0057]
[0058] Table 2 Main chemical components of Baiyun tailings
[0059]
[0060] Preparation Example 2: (1) 900 g of copper tailings, 100 g of fly ash from the incineration of domestic waste, 25 g of Baiyun tailings and 60 g of sawdust were mixed evenly, and dried at 180° C. for 2 h to obtain a solid waste raw material;
[0061] (2) adding 20 wt% of water to the solid waste raw material and mixing them evenly to form a wet material;
[0062] (3) granulating the wet material to obtain raw material balls with a particle size of 5 mm;
[0063] (4) The raw material balls are dried at 100°C for 5 hours, then preheated at 340°C for 30 minutes, and sintered at 1100°C for 20 minutes to obtain more solid waste ceramsite.
[0064] Preparation Example 3: The difference from Preparation Example 1 is that an equal amount of stone powder is used to replace wood chips. The calcium carbonate content in the stone powder is above 99.5%, and the density is 2700kg / m 3 .
[0065] Preparation Example 4: The difference from Preparation Example 1 is that no dolomite tailings were added.
[0066] According to Preparation Examples 1-4, prepared multi-solid waste ceramsite, referring to GB / T17431.2-2010 "Test Methods for Light Aggregates" to test bulk density, apparent density, porosity, water absorption and cylinder compressive strength, using a 300KN universal testing press, taking the average strength of 10 multi-solid waste ceramsite as the test result, and calculating the single compressive strength according to the following formula: F = 2.8P / (πd 2 ), where F is the compressive strength of a single particle of multi-solid waste ceramsite (MPa), P is the maximum instantaneous pressure of multi-solid waste ceramsite crushing (N), and is the diameter of the vertical pressure-bearing surface of multi-solid waste ceramsite (mm). The test results are recorded in Table 3.
[0067] Table 3 Performance test of multi-solid waste ceramsite
[0068]
[0069] As can be seen in Table 3, when stone powder is used as a porogen, the calcium carbonate in it decomposes when heated to release a large amount of carbon dioxide. At high temperature, the stone powder can react with silicon dioxide to form calcium silicate, resulting in a decrease in the silicon dioxide content, a decrease in the content of mullite crystals, and a decrease in strength. Without adding dolomite tailings to form a liquid phase, the porosity is reduced.
[0070] Preparation Example 5-12 of Hydrophobically Modified Polyester Fiber
[0071] Preparation Example 5: 30 g of silane-modified silica particles were mixed with 80 g of butyl acetate, ultrasonically dispersed at a power of 200 W for 30 min, 20 g of polyurea resin and 10 g of curing agent were added, and stirred evenly to obtain a treatment liquid. The polyurea resin was polyaspartic acid ester polyurea, selected from Hunan Tuochuang Polymer New Materials, model 283, and solid content of 50%. The curing agent was selected from Covestro of Germany, model N75. The preparation method of silane-modified silica particles was as follows: 30 ml of anhydrous ethanol, 30 ml of toluene and 2 ml of perfluorooctyltriethoxysilane were mixed, the pH was adjusted to 9, silica particles were added, ultrasonicated for 20 h, stirred at 60 ° C for 5 h, centrifuged, washed, and dried;
[0072] The treatment liquid was sprayed evenly on the polyester fiber and dried at 85°C for 8 hours to obtain modified polyester fiber. The length of the polyester fiber was 12 mm and the diameter was 20 μm. The mass ratio of the treatment liquid to the polyester fiber was 0.3:1.
[0073] Preparation Example 6: 40 g of silane-modified silica particles were mixed with 90 g of butyl acetate, ultrasonically dispersed at a power of 200 W for 20 min, 30 g of polyurea resin and 15 g of curing agent were added, and stirred evenly to obtain a treatment liquid. The polyurea resin was polyaspartic acid ester polyurea, selected from Hunan Tuochuang Polymer New Materials, model 283, and solid content of 50%. The curing agent was selected from Covestro of Germany, model N75. The preparation method of silane-modified silica particles was as follows: 30 ml of anhydrous ethanol, 30 ml of toluene and 2 ml of perfluorooctyltriethoxysilane were mixed, the pH was adjusted to 9, silica particles were added, ultrasonicated for 20 h, stirred at 60 ° C for 5 h, centrifuged, washed, and dried;
[0074] The treatment liquid was sprayed evenly on the polyester fiber and dried at 80°C for 10 hours to obtain modified polyester fiber. The length of the polyester fiber was 12 mm and the diameter was 20 μm. The mass ratio of the treatment liquid to the polyester fiber was 0.1:1.
[0075] Preparation Example 7: The difference from Preparation Example 5 is that no silane-modified silica particles are added.
[0076] Preparation Example 8: The difference from Preparation Example 5 is that the silicon dioxide particles are not subjected to silane modification treatment.
[0077] Preparation Example 9: The difference from Preparation Example 5 is that the silane-modified silica particles are prepared by the following method: 10 ml of anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1, and an appropriate amount of glacial acetic acid is added to prepare a mixed solution A; 20 ml of anhydrous ethanol, 100 mg of silica phase change capsules and 500 μl of tetrabutyl titanate are mixed to prepare a solution B, the wall material of the silica phase change capsules is silica, and the core material is tetradecane. The preparation method is: 5 g of tetradecane, 1 g of hexadecyltrimethylammonium bromide, 30 g of deionized water and 35 g of anhydrous ethanol are mixed to obtain an emulsion, 6 g of tetraethyl orthosilicate and 12 g of ammonia water are added, and the reaction is stirred at 60°C for 5 hours, filtered, washed and vacuum dried;
[0078] Solution B was added to solution A, reacted at 200°C for 24 hours, centrifuged, washed, dried, and calcined at 500°C for 2 hours to obtain modified silica phase change capsules;
[0079] 30 ml of anhydrous ethanol, 30 ml of toluene and 2 ml of perfluorooctyltriethoxysilane were mixed, the pH was adjusted to 9, the modified silica phase change capsules were added, ultrasonicated for 20 h, stirred at 60° C. for 5 h, centrifuged, washed and dried to obtain silane-modified silica particles.
[0080] Preparation Example 10: The difference from Preparation Example 5 is that the silane-modified silica particles are prepared by the following method: 10 ml of anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1, and an appropriate amount of glacial acetic acid is added to prepare a mixed solution A; 20 ml of anhydrous ethanol, 100 mg of silica phase change capsules and 500 μl of tetrabutyl titanate are mixed to prepare a solution B, the wall material of the silica phase change capsules is silica, and the core material is tetradecane. The preparation method is: 5 g of tetradecane, 1 g of hexadecyltrimethylammonium bromide, 30 g of deionized water and 35 g of anhydrous ethanol are mixed to obtain an emulsion, 6 g of tetraethyl orthosilicate and 12 g of ammonia water are added, and the mixture is stirred at 60°C for 5 h, filtered, washed and vacuum dried;
[0081] Solution B was added to solution A, reacted at 220°C for 20 hours, centrifuged, washed, dried, and calcined at 450°C for 3 hours to obtain modified silica phase change capsules;
[0082] 30 ml of anhydrous ethanol, 30 ml of toluene and 2 ml of perfluorooctyltriethoxysilane were mixed, the pH was adjusted to 9, the modified silica phase change capsules were added, ultrasonicated for 30 hours, stirred at 65° C. for 6 hours, centrifuged, washed and dried to obtain silane-modified silica particles.
[0083] Preparation Example 11: The difference from Preparation Example 9 is that tetrabutyl titanate is not added.
[0084] Preparation Example 12: The difference from Preparation Example 9 is that silica particles are used instead of silica phase change capsules.
[0085] Example
[0086] Example 1: An environmentally friendly rubber asphalt material prepared by the synergistic use of multiple solid wastes, the raw material dosage is shown in Table 4, wherein the elastomer modified asphalt is SBS modified asphalt, the SBS modified asphalt is selected from Foshan Chuanglixin Chemical, and the item number is ID, the waste rubber powder is obtained by mixing waste tires and EPDM rubber in a mass ratio of 1:0.5, crushing, deironing, and grinding to 5 mm, SBR is selected from Xiamen Mingjia New Materials, model SBR1502, the stabilizer is butyl rubber, selected from Jiangsu Guanfu New Materials, brand GF2022, item number G111f8x, the anti-stripping agent is selected from Jinan Xichuan Chemical Technology, model XC-067, the multi-solid waste ceramsite is made from Preparation Example 1, and the tackifier is hydrogenated C9 petroleum resin, selected from Guangzhou Linli New Materials, item number 1113, model HPR-C9100.
[0087] The preparation process of the environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes comprises the following steps: mixing elastomer-modified asphalt and aromatic oil, heating to 160° C., adding waste rubber, mixing and stirring for 40 minutes to obtain a binder;
[0088] The binder temperature was maintained at 160°C, and solid waste expanded clay, stabilizer, anti-stripping agent and tackifier were added, mixed and stirred for 40 minutes to obtain an environmentally friendly rubber asphalt material.
[0089] Table 4 Raw material usage of environmentally friendly rubber asphalt materials
[0090]
[0091]
[0092] Example 2: An environmentally friendly rubber asphalt material prepared by the synergistic use of multiple solid wastes, the raw material dosage is shown in Table 4, wherein the elastomer modified asphalt is SBS modified asphalt, the SBS modified asphalt is selected from Foshan Chuanglixin Chemical, and the item number is ID, the waste rubber powder is obtained by mixing waste tires and EPDM rubber in a mass ratio of 1:0.5, crushing, deironing, and grinding to 5 mm, SBR is selected from Xiamen Mingjia New Materials, model SBR1502, the stabilizer is butyl rubber, selected from Jiangsu Guanfu New Materials, brand GF2022, item number G111f8x, the anti-stripping agent is selected from Jinan Xichuan Chemical Technology, model XC-067, the multi-solid waste ceramsite is made from Preparation Example 2, and the tackifier is hydrogenated C9 petroleum resin, selected from Guangzhou Linli New Materials, item number 1113, model HPR-C9100.
[0093] The preparation process of the environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes comprises the following steps: mixing elastomer-modified asphalt and aromatic oil, heating to 170° C., adding waste rubber, mixing and stirring for 30 minutes to obtain a binder;
[0094] The binder temperature was maintained at 170°C, and solid waste expanded clay, stabilizer, anti-stripping agent and tackifier were added, mixed and stirred for 30 minutes to obtain an environmentally friendly rubber asphalt material.
[0095] Example 3-4: An environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes. The difference from Example 1 is that the amounts of raw materials used are as shown in Table 4.
[0096] Example 5: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 1 is that the multi-solid waste expanded clay is prepared by Preparation Example 3.
[0097] Example 6: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 1 is that the multi-solid waste expanded clay is prepared by Preparation Example 4.
[0098] Example 7: An environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes. The difference from Example 1 is that the multiple solid waste ceramsite is pretreated as follows:
[0099] Dissolve sodium chloride in deionized water to prepare a sodium chloride solution with a concentration of 20 wt%, add sodium dodecyl sulfate, mix well, and obtain a soaking solution, wherein the mass ratio of sodium dodecyl sulfate to sodium chloride is 0.025:1;
[0100] Adding the solid waste ceramsite into the soaking solution, soaking for 5 hours at 45°C, filtering and drying, and obtaining the salt-loaded ceramsite;
[0101] Anhydrous ethanol and distilled water were mixed in a mass ratio of 60:1, the pH was adjusted to 3, 6.7% of hexadecyltrimethoxysilane was added, and the spraying liquid was obtained by stirring at room temperature. The spraying liquid was evenly sprayed on the salt-loaded ceramsite and allowed to stand at room temperature for 24 hours. The mass ratio of the spraying liquid to the salt-loaded ceramsite was 0.2:1.
[0102] Example 8: An environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes. The difference from Example 1 is that the ceramsite from multiple solid wastes is pretreated as follows:
[0103] Dissolve sodium chloride in deionized water to prepare a sodium chloride solution with a concentration of 15 wt%, add sodium dodecyl sulfate, mix well, and obtain a soaking solution, wherein the mass ratio of sodium dodecyl sulfate to sodium chloride is 0.015:1;
[0104] Adding the solid waste ceramsite into the soaking solution, soaking for 7 hours at 35°C, filtering and drying, and obtaining the salt-loaded ceramsite;
[0105] Anhydrous ethanol and distilled water were mixed in a mass ratio of 55:1, the pH was adjusted to 2, 6.5% of hexadecyltrimethoxysilane was added, and the spraying liquid was obtained by stirring at room temperature. The spraying liquid was evenly sprayed on the salt-loaded ceramsite and allowed to stand at room temperature for 20 hours. The mass ratio of the spraying liquid to the salt-loaded ceramsite was 0.1:1.
[0106] Example 9: An environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes. The difference from Example 7 is that the ceramsite from multiple solid wastes is pretreated as follows:
[0107] Mix anhydrous ethanol and distilled water in a mass ratio of 60:1, adjust the pH to 3, add 6.7% of hexadecyltrimethoxysilane, stir at room temperature to obtain a spray liquid, spray the spray liquid evenly on the multi-solid waste expanded clay, and let it stand at room temperature for 24 hours. The mass ratio of the spray liquid to the multi-solid waste expanded clay is 0.2:1.
[0108] Example 10: An environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes. The difference from Example 7 is that the multiple solid waste ceramsite is pretreated as follows:
[0109] Dissolve sodium chloride in deionized water to prepare a sodium chloride solution with a concentration of 20 wt%, add sodium dodecyl sulfate, mix well, and obtain a soaking solution, wherein the mass ratio of sodium dodecyl sulfate to sodium chloride is 0.025:1;
[0110] Add the solid waste ceramsite into the soaking solution, soak at 45℃ for 5h, filter and dry.
[0111] Example 11: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 7 is that the anti-stripping agent is modified polyester fiber, and the modified polyester fiber is made from Preparation Example 5.
[0112] Example 12: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 7 is that the anti-stripping agent is modified polyester fiber, and the modified polyester fiber is made from Preparation Example 6.
[0113] Example 13: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 11 is that the modified polyester fiber is made from Preparation Example 7.
[0114] Example 14: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 11 is that the modified polyester fiber is made from Preparation Example 8.
[0115] Example 15: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 11 is that the modified polyester fiber is made from Preparation Example 9.
[0116] Example 16: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 11 is that the modified polyester fiber is made from Preparation Example 10.
[0117] Example 17: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 15 is that the modified polyester fiber is made from Preparation Example 11.
[0118] Example 18: An environmentally friendly rubber asphalt material prepared by co-production of multiple solid wastes. The difference from Example 15 is that the modified polyester fiber is made from Preparation Example 12.
[0119] Comparative Example
[0120] Comparative Example 1: An environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes. The difference from Example 1 is that an equal amount of filled ceramsite is used to replace the multiple solid waste ceramsite. The filled ceramsite is a commercially available product selected from Anhui Changcai Energy Saving Technology. The material is shale, clay and rice husk, the particle size is 5-15mm, and the apparent density is 750kg / m 3 , bulk density is 450kg / m 3, water absorption is 13%, porosity is 40%, and cylinder pressure strength is 2.5MPa.
[0121] Performance testing
[0122] The rubber asphalt material was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following methods. The test results are recorded in Table 5.
[0123] 1. Dynamic stability: Tested according to the standard method specified in JTJ052-2000 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".
[0124] 2. Dynamic modulus: Tested in accordance with ASTM D7552-22 "Standard Test Method for Composite Shear Modulus of Asphalt Mixtures Using Dynamic Shear Rheometer".
[0125] 3. Permeability coefficient: Test in accordance with CJJ / T135-200 "Technical Code for Permeable Cement Concrete Pavement".
[0126] 4. Low temperature resistance: -10°C was selected as the freeze-thaw temperature. Four parallel specimens were set for each embodiment or comparative example. The specimens were 63.5 mm in height and 101.6 mm in diameter. The rubber asphalt material was mixed evenly and then cooled and cured at room temperature for at least 12 hours. The prepared specimens were cut and the specimens were 30.5 mm in thickness and 101.6 mm in diameter. In order to better simulate the state of the rubber asphalt pavement being immersed in water in winter, the specimens were immersed in salt water and clean water at room temperature and pressure until the mass of the specimens no longer changed. The saturation time of the specimen is set to 100h; the specimen is placed in a plastic bag and injected with 10mL of Qingshui River saline solution, frozen in a -20℃ low-temperature box for 13h, then the plastic bag is removed and placed in a 40℃ water bath to thaw for 11h, which is one freeze-thaw cycle, and a total of 8 freeze-thaw cycles are performed; after the freeze-thaw cycle, the specimen is placed in a dry and ventilated place, dried at room temperature for 24h, and then placed in a low-temperature box for no less than 4h, the temperature is controlled at -10℃, loaded at a speed of 5mm / min, the test force and deformation measurement accuracy is ±1%, and the ultimate load is tested.
[0127] Table 4 Performance test of environmentally friendly rubber asphalt materials
[0128]
[0129]
[0130] Combining the data in Table 4 with Examples 1-4, it can be seen that the multi-solid waste expanded clay prepared in Preparation Example 1 and Preparation Example 2 can be made into rubber asphalt materials with high water permeability, high dynamic stability, large dynamic modulus, strong rutting resistance and crack resistance.
[0131] In Example 5 and Example 6, the multi-solid waste expanded clay prepared in Preparation Example 3 and Preparation Example 4 were used respectively. Compared with Preparation Example 1, stone powder was used instead of sawdust, and no dolomite tailings were added. It can be seen from the data in Table 4 that although the water permeability coefficient of the rubber asphalt materials prepared in Example 5 and Example 6 increased, the dynamic stability decreased, the dynamic modulus decreased, and the anti-rutting ability and anti-cracking effect became worse.
[0132] Compared with Example 1, Examples 7 and 8 use sodium chloride, sodium dodecyl sulfate, etc. to pretreat the multi-solid waste expanded clay. It can be seen that after freeze-thaw cycles under clean water conditions, the ultimate load of the rubber asphalt material is stronger than that of Example 1. However, due to the addition of sodium chloride, its ultimate load in the brine solution decreases due to the corrosion of the brine solution.
[0133] Compared with Example 7, Example 9 does not load sodium chloride in the multi-solid waste expanded clay. It can be seen that after 8 freeze-thaw cycles in clean water, the ultimate load increases, while the ultimate load in the saline solution increases, indicating that sodium chloride can improve the anti-icing effect of the rubber asphalt material at low temperatures.
[0134] Compared with Example 7, Example 10 does not add hexadecyltrimethoxysilane. The data in Table 4 show that the water permeability coefficient of the rubber asphalt material prepared in Example 10 is reduced, and after the fresh water freezing cycle, the ultimate load is reduced, and the ultimate load in the saline solution also decreases, indicating that hexadecyltrimethoxysilane can increase the hydrophobicity of the rubber asphalt, reduce water retention, and reduce crystallization expansion.
[0135] Compared with Example 7, Example 11 and Example 12 also use the modified polyester fibers prepared in Preparation Examples 5 and 6 as anti-stripping agents. It can be seen that the dynamic stability and dynamic modulus of the asphalt materials prepared in Example 11 and Example 12 are increased, the water permeability coefficient is higher, the water permeability is stronger, and the freeze-thaw resistance and anti-icing effects are improved.
[0136] In Example 13, the modified polyester fiber prepared in Preparation Example 7 was used. Compared with Example 11, no silane-modified silica particles were added. The anti-freeze-thaw effect of the rubber asphalt material prepared in Example 13 was reduced, and the dynamic stability and dynamic modulus were reduced, indicating that silane-modified silica particles can improve the mechanical strength and anti-seepage and anti-freeze effects of the rubber asphalt material.
[0137] Example 14 uses the modified polyester fiber prepared in Preparation Example 8. Compared with Example 11, the silica particles are not treated with silane. The tensile stability and dynamic modulus of the rubber asphalt material prepared in Example 14 are slightly weakened, the water permeability coefficient is reduced, and the anti-freeze-thaw effect is reduced.
[0138] Compared with Example 11, Examples 15 and 16 respectively use the modified polyester fibers prepared in Preparation Examples 9 and 10, and the silane-modified silica particles are modified silica phase change capsules. It can be seen from the data in Table 4 that the materials prepared in Examples 15 and 16 have excellent anti-freezing effects and can reduce the strength loss in freeze-thaw environments.
[0139] In Example 17, the modified polyester fiber prepared in Preparation Example 11 was used without adding tetrabutyl titanate. It can be seen that compared with Example 15, the strength of the rubber asphalt material prepared in Example 17 is reduced and the anti-freeze-thaw effect is weakened.
[0140] In Example 18, the modified polyester fiber prepared in Preparation Example 12 was used. Compared with Example 15, the clear water and salt water ultimate loads of the asphalt material were both reduced, indicating that silica can improve the anti-freeze-thaw effect compared with capsules.
[0141] Comparative Example 1 uses commercially available expanded clay to replace solid waste expanded clay. It can be seen that the dynamic stability of the rubber asphalt material prepared in Comparative Example 1 decreases, the dynamic modulus decreases, the water permeability coefficient is high, and the antifreeze effect becomes worse.
[0142] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes, characterized in that: The method comprises the following raw materials in parts by weight: 100-140 parts of elastomer modified asphalt, 15-25 parts of waste rubber powder, 0.5-1 parts of SBR, 1-3 parts of stabilizer, 1.5-3 parts of anti-stripping agent, 30-50 parts of multi-solid waste ceramsite, 10-14 parts of aromatic oil, and 5-15 parts of tackifier; The waste rubber powder is prepared by mixing and crushing waste tires and EPDM rubber in a mass ratio of 1:0.3-0.5; The multi-solid waste expanded clay is prepared by adding water to solid waste raw materials to form wet materials, followed by granulation, drying, preheating at 340-350° C. for 20-30 minutes, and sintering at 1050-1100° C. for 20-30 minutes. The solid waste raw materials include copper tailings, domestic waste incineration fly ash, white cloud tailings and sawdust in a mass ratio of 9:1:0.25-0.5:0.6-1.
2. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 1, characterized in that: The preparation method of the multi-solid waste ceramsite is as follows: The copper tailings are mixed evenly with waste incineration fly ash, Baiyun tailings and wood chips to obtain solid waste raw materials; Adding 20-30 wt% of water to the solid waste raw material and mixing them evenly to form a wet material; Granulating the wet material to obtain raw material balls with a particle size of 5-9 mm; The raw material balls are dried at 100-110° C. for 4-5 hours, then preheated at 340-350° C. for 20-30 minutes, and sintered at 1050-1100° C. for 20-30 minutes to prepare multi-solid waste ceramsite.
3. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 2, characterized in that: The multi-solid waste ceramsite is subjected to the following pretreatment: Dissolve sodium chloride to prepare a sodium chloride solution with a concentration of 15-20wt%, add sodium dodecyl sulfate, mix well, and obtain a soaking solution, wherein the mass ratio of sodium dodecyl sulfate to sodium chloride is 0.015-0.025:1; Adding the solid waste ceramsite into the soaking solution, soaking for 5-7 hours at 35-45°C, filtering and drying to obtain the salt-loaded ceramsite; Mix anhydrous ethanol and distilled water in a mass ratio of 55-60:1, adjust the pH to 2-3, add 6.5-6.7% of hexadecyltrimethoxysilane by mass, stir at room temperature to obtain a spray liquid, spray the spray liquid evenly on the salt-loaded ceramsite, and let it stand at room temperature for 20-24 hours. The mass ratio of the spray liquid to the salt-loaded ceramsite is 0.1-0.2:
1.
4. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 1, characterized in that: The anti-stripping agent is hydrophobically modified polyester fiber.
5. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 4, characterized in that: The preparation method of the hydrophobically modified polyester fiber: The silane-modified silica particles are mixed with butyl acetate, and ultrasonically dispersed for 20-30 minutes, and polyurea resin and curing agent are added, and stirred to obtain a treatment liquid; The treatment liquid is sprayed on the polyester fiber, and dried at 80-85° C. for 8-10 hours to obtain the modified polyester fiber.
6. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 5, characterized in that: The mass ratio of the silane-modified silica particles, butyl acetate, polyurea resin and curing agent is 3-4:8-9:2-3:1-1.5; the mass ratio of the treatment liquid to the polyester fiber is 0.1-0.3:
1.
7. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 5, characterized in that: The preparation method of the silane-modified silica particles: Anhydrous ethanol and deionized water are mixed, and glacial acetic acid is added to prepare a mixed solution A; anhydrous ethanol, silicon dioxide phase change capsules and tetrabutyl titanate are mixed to prepare a solution B; Add solution B to solution A, react at 200-220°C for 20-24h, centrifuge, wash, dry, and calcine at 450-500°C for 2-3h to obtain modified silica phase change capsules; Anhydrous ethanol, toluene and perfluorooctyltriethoxysilane are mixed, the pH is adjusted to 9, modified silica phase change capsules are added, ultrasonication is performed for 20-30 minutes, stirring is performed at 60-65° C. for 5-6 hours, centrifugation is performed, washing is performed, and drying is performed to obtain silane-modified silica particles.
8. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 7, characterized in that: The wall material of the silicon dioxide phase change capsule is silicon dioxide, and the core material is tetradecane.
9. The environmentally friendly rubber asphalt material prepared by synergistic use of multiple solid wastes according to claim 1, characterized in that: The tackifier is selected from at least one of petroleum resin, liquid coumarone, terpene resin and rosin resin.
10. The process for preparing the environmentally friendly rubber asphalt material prepared by synergistically using multiple solid wastes as described in any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing elastomer-modified asphalt and aromatic oil, heating to 160-170° C., adding waste rubber, mixing and stirring for 30-40 minutes, and obtaining a binder; The binder temperature is maintained at 160-170°C, and solid waste expanded clay, stabilizer, anti-stripping agent and tackifier are added, mixed and stirred for 40-60 minutes to obtain an environmentally friendly rubber asphalt material.
Citation Information
Patent Citations
Multifunctional permeable asphalt mixture and preparation method thereof
CN107129195A
High-water-permeability solid waste environment-friendly rubber asphalt material and preparation method thereof
CN117534369A
Multifunctional iron tailing asphalt pavement material and preparation method thereof
CN118878253A
Method for preparing ceramsite through multi-element solid waste co-treatment and application
CN120081608A
Modified asphalt-based eco-friendly composition for rapid repairing road pavement using recycled lightweight aggregate and manufacturing method thereof
KR102416515B1